Fly ash-based dredged sludge dewatering and curing integrated medicament as well as preparation method and application thereof
The fly ash-based integrated agent effectively addresses the challenges of high water content and heavy metals in dredged sludge by using modified fly ash and starch-acrylonitrile graft copolymer to achieve high dehydration and solidification rates, reducing costs and environmental impact.
Patent Information
- Application Number
- CN202411505630.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-28
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2044-10-28
AI Technical Summary
Current methods for dredged sludge treatment face challenges such as high water content, high compressibility, low permeability, and the presence of heavy metals and odorous gases, leading to high costs and inefficient disposal, particularly in large-scale dredging operations.
A fly ash-based dehydration and solidification integrated agent is developed using modified fly ash, tetraethyl orthosilicate, rhodamine B, and starch-acrylonitrile graft copolymer, prepared through surface modification, low-temperature roasting, and reaction grafting, to efficiently absorb and solidify water and heavy metals.
The agent achieves high dehydration and solidification rates, with a 95% dehydration rate and 98% heavy metal removal, while being cost-effective and environmentally friendly, utilizing fly ash's porosity and starch-acrylonitrile's osmotic pressure to remove moisture and heavy metals.
Abstract
Description
Technical Field
[0001] The invention relates to a fly ash-based dredged sludge dehydration and solidification integrated agent, a preparation method and application thereof, and belongs to the field of environmentally friendly materials and sludge treatment. Background Art
[0002] With the rapid development of urbanization and industrialization, the problem of siltation in rivers, lakes, ports and other water bodies has become increasingly serious, and dredging has become an important means to maintain the function of water bodies. According to reports, an average of about 1.4 billion tons of silt accumulates in reservoirs, rivers, lakes and irrigation canals in my country every year, and 1.8 billion tons of silt enters estuaries and oceans, resulting in a large demand for dredging.
[0003] There are mainly sanitary landfill, incineration, aerobic composting, building materials utilization and other methods for the disposal of dredged sludge. Its main goal is to reduce, harmlessly treat, stabilize and recycle it. Drying and solidification are one of the essential key links in the dredged sludge disposal process. They can effectively reduce the water content, reduce the transportation, storage and subsequent treatment costs, and play an important role in achieving the reduction, harmlessness, stabilization and recycle of high-water wastes such as dredged sludge. However, dredged sludge often has the characteristics of high water content, high compressibility, low permeability, and heavy metals and odorous gases. As a result, the equipment for drying sludge has problems such as long sludge transportation distance, large investment in drying equipment, high operating energy consumption, and poor equipment stability. It is difficult to meet the current situation of my country's large dredged sludge production, wide distribution, high water content and scattered distribution.
[0004] In addition, the current treatment of dredged sludge usually adopts the method of first dehydrating and drying and then solidifying heavy metal ions and odorous gases, which will further increase the disposal cost, and the dehydration agent or technology and the solidification agent or technology also need to comprehensively consider the cost and efficiency to promote the reduction and resource utilization of dredged sludge. Therefore, the development of efficient dehydration and solidification integrated agents for dredged sludge has important scientific research value and social significance. Summary of the invention
[0005] The purpose of the present invention is to propose a fly ash-based dehydration and solidification integrated agent for dredged sludge in view of the current situation and existing problems in the field of dredged sludge treatment. Another purpose of the present invention is to provide a preparation method of the above-mentioned agent.
[0006] A fly ash-based dredged sludge dehydration and solidification integrated agent, the agent uses modified fly ash as a base, tetraethyl orthosilicate and rhodamine B as grafting agents, starch-acrylonitrile grafting copolymer as a dehydrating agent, ammonium cerium sulfate as an initiator, and is prepared by a surface modification-low temperature roasting coating-reaction grafting combined method; based on the mass of the modified fly ash base, the mass percentage of the grafting agent is 10% to 30%, the mass percentage of the dehydrating agent is 20% to 50%, and the mass percentage of the initiator is 1% to 10%.
[0007] The above-mentioned fly ash-based dredged sludge dehydration and solidification integrated agent: based on the mass of the fly ash base, the mass percentage of the grafting agent is 10% to 30%, the mass percentage of the dehydrating agent is 30% to 50%, and the mass percentage of the initiator is 1% to 2%.
[0008] A method for preparing a fly ash-based dredged sludge dehydration and solidification integrated agent, the preparation method of the agent is as follows:
[0009] (1) Surface modification of fly ash
[0010] The fly ash is soaked in an acid solution and an alkaline solution successively and then filtered, and then washed and dried in sequence after filtering to obtain pretreated fly ash, and the pretreated fly ash is treated with plasma to obtain modified fly ash;
[0011] (2) Rhodamine B grafting
[0012] Tetraethyl orthosilicate is added to rhodamine B solution and mixed, and then a dilute hydrochloric acid solution is added to hydrolyze and condense tetraethyl orthosilicate to form a grafting solution, and the surface-modified fly ash is placed in the grafting solution for 5 to 10 seconds, then filtered out and placed in an oven for drying, and finally calcined to form a mixed substrate;
[0013] (3) Integrated pharmaceutical preparation
[0014] After heating and cooling, add ammonium cerium sulfate, acrylonitrile monomer and the mixed base prepared in step (2) to the starch slurry, mix well and react, add acetone after the reaction is completed and continue stirring, finally let it stand for 2 to 4 hours and then filter and dry to obtain a fly ash-based dredged sludge dehydration and solidification integrated agent.
[0015] In the above preparation method: the dilute hydrochloric acid solution described in step (1) is a hydrochloric acid solution with a mass fraction of 3% to 7%, and the mass fraction of the sodium hydroxide solution is 1 to 10%; the soaking time is 4 to 8 hours; the drying temperature is 80 to 100° C., and the drying time is 6 to 12 hours.
[0016] In the above preparation method: the plasma surface treatment instrument described in step (1) is Plasma clean-PL-5010, the input voltage during surface treatment is 220V, the working distance is 5-12mm, the treatment atmosphere is oxygen, and the plasma flame scanning rate is 20-100mm / s.
[0017] In the above preparation method: the mass ratio of rhodamine B and tetraethyl orthosilicate in step (2) is 1:(0.1-0.2); the dilute hydrochloric acid solution is a hydrochloric acid solution with a molar fraction of 3%-7%, and the mass ratio of tetraethyl orthosilicate to the dilute hydrochloric acid solution is 1:(50-100).
[0018] In the above preparation method: the drying temperature in step (2) is 25-40° C., and the drying time is 3-6 hours; the roasting temperature is 160-200° C., and the roasting time is 2-4 hours.
[0019] In the above preparation method: in step (3), the mass concentration of starch slurry is 1-10%, and the mass ratio of starch slurry to acrylonitrile is 3-8:1.
[0020] In the above preparation method: in step (3), the starch is heated to 85-95°C for 2-4 hours and then cooled to room temperature; the reaction temperature is 20-40°C for 2-4 hours; the drying temperature is 40-60°C for 6-12 hours.
[0021] In the technical solution of the present invention, the agent is used in the field of dredged sludge dehydration and reduction.
[0022] The performance conditions and results of the present invention are as follows: 100 g of soil slurry (wherein the mass concentration of soil is 40%, ZnCl 2 10g of the integrated agent was added and stirred for 3min until the agent absorbed the water in the slurry. Then 10g of wet soil was placed in 100g of deionized water and stirred for 1h to form a purified soil slurry. Then, an inductively coupled plasma mass spectrometer was used to determine the Zn content in the purified soil slurry. 2+ The ion concentration is calculated from Zn 2+ Solidification removal rate, then take 10g of wet soil and place it in an oven at 100℃ for 10h to dry it, then calculate the moisture content of the wet soil, and calculate the dehydration rate of the agent for the soil slurry based on the moisture content of the wet soil; the agent is at room temperature and pressure, Zn 2+ The solidification removal rate reaches 98%, and the soil slurry dehydration rate can reach 95%.
[0023] Beneficial effects:
[0024] The agent prepared by the present invention can efficiently remove moisture and heavy metal ions from dredged sludge, achieve the reduction of dredged sludge and the solidification of heavy metal ions. Compared with the prior art, the agent uses modified fly ash as the base, which can not only utilize the high water absorption and high porosity of fly ash to quickly absorb water molecules and heavy metal ions, but also realize the high added value resource utilization of low-value fly ash, and reduce the cost of the agent; using starch-acrylonitrile graft copolymer as a dehydrating agent, it can not only utilize the large number of hydroxyl groups of starch itself to form hydrogen bonds with water molecules to absorb moisture, but also utilize the three-dimensional network structure formed by the swelling of starch-acrylonitrile graft copolymer in water to absorb and store a large amount of moisture, and after the starch-acrylonitrile graft copolymer swells in water, its internal ion concentration is higher than the external solution ion concentration, thereby generating osmotic pressure, further driving water molecules into the network structure, and finally the hydrophilic groups such as carboxyl groups of starch-acrylonitrile graft copolymer ionize in water to generate charged ions, which can inhibit water molecules and heavy metal ions from leaving the integrated structure. inside the agent; because fly ash is an inorganic substance and starch-acrylonitrile graft copolymer is an organic substance, it is difficult for starch-acrylonitrile graft copolymer to grow on the surface of fly ash and inside the pores under conventional methods. Therefore, tetraethyl orthosilicate and rhodamine B are used as grafting agents, and the hydrolysis and condensation of tetraethyl orthosilicate is used to solidify rhodamine B, so that tetraethyl orthosilicate is coupled with rhodamine B and a thin film is formed on the surface of the modified fly ash substrate and inside the pores. The modified fly ash substrate and the starch-acrylonitrile graft copolymer are grafted by the film to achieve efficient synergistic effect of the starch-acrylonitrile graft copolymer and the modified fly ash substrate; in the process of tetraethyl orthosilicate forming a thin film solution with rhodamine B, a dilute hydrochloric acid solution is used to promote the hydrolysis and condensation of tetraethyl orthosilicate and form a linear or branched polymer, so that the thin film solution of tetraethyl orthosilicate and rhodamine B is not only a physical coating but also has the effect of chemical bond chains. Therefore, the agent of the present invention can adsorb and remove moisture and heavy metal ions in dredged sludge at room temperature and realize solidification, thereby avoiding the precipitation of heavy metal ions and finally realizing the drying, solidification and reduction of dredged sludge. Moreover, the agent components are environmentally friendly, the preparation process is simple, the cost is low, the cost performance is high, and it has strong application and promotion value. DETAILED DESCRIPTION
[0025] The present invention is further described below in conjunction with the embodiments, but the protection scope of the present invention is not limited thereto: Embodiment 1
[0026] (1) Surface modification of fly ash
[0027] Weigh 20.000g of fly ash and add 400.000g of deionized water and 40.000g of 3% dilute hydrochloric acid solution to soak for 8h and let stand before filtering, then add 400.000g of deionized water and 20.000g of sodium hydroxide to soak for 8h and let stand before filtering, add 1000.000g of deionized water to wash three times and then filter and place in an oven at 80°C to dry for 12h to obtain fly ash after acid and alkali washing, then measure 2mL of fly ash after acid and alkali washing and place it in a plasma surface treatment instrument (Plasma clean-PL-5010 model, the same below), first evacuate the plasma surface treatment instrument, then fill it with 40mL of oxygen, and then perform surface treatment under the conditions of an input voltage of 220V, a working distance of 5mm, and a plasma flame scanning rate of 20mm / s to obtain surface-modified fly ash, and repeat the plasma surface modification steps until the fly ash after acid and alkali washing is used up;
[0028] (2) Rhodamine B grafting
[0029] 0.909 g of rhodamine B was weighed and dissolved in 27.270 g of ethanol to form a rhodamine B solution, and 0.091 g of tetraethyl orthosilicate was weighed and added to the rhodamine B solution, and the mixed solution was placed on a magnetic heating stirrer and stirred at 25° C. for 4 h, and then 9.100 g of a 3% by mass dilute hydrochloric acid solution was added dropwise to hydrolyze and condense the tetraethyl orthosilicate to form a grafting solution, 10.000 g of the surface-modified fly ash obtained in step (1) was weighed and placed in the grafting solution for 5 seconds, then filtered out and placed in an oven for low-temperature drying at 25° C. for 6 h, and the surface-modified fly ash was repeatedly placed in the grafting solution and dried until the grafting solution was consumed, and finally placed in a muffle furnace for low-temperature baking at 160° C. for 4 h to form a mixed substrate;
[0030] (3) Integrated pharmaceutical preparation
[0031] Weigh 0.500 g of starch and add 10 g of deionized water to form a starch slurry, heat in a water bath at 85° C. for 4 h, and then cool to room temperature. Then add 0.100 g of ammonium cerium sulfate, 2.500 g of acrylonitrile monomer and 10.000 g of the mixed base prepared in step (2), and place the mixed slurry on a magnetic heating stirrer and heat in a water bath at 20° C. for reaction for 4 h. After the reaction is completed, add 15.000 g of acetone and continue stirring. Finally, let it stand for 2 h, filter it, and dry it in an oven at 40° C. for 12 h to obtain a fly ash-based dredged sludge dehydration and solidification integrated agent.
[0032] (4) Performance evaluation test
[0033] Take 100g of soil slurry (where the mass concentration of soil is 40%, ZnCl 210g of the integrated agent was added and stirred for 3min until the agent absorbed the water in the slurry. Then 10g of wet soil was placed in 100g of deionized water and stirred for 1h to form a purified soil slurry. Then, an inductively coupled plasma mass spectrometer was used to determine the Zn content in the purified soil slurry. 2+ The ion concentration is calculated from Zn 2+ Solidification removal rate, then take 10g of wet soil and place it in an oven at 100℃ for 10h to dry it, then calculate the moisture content of the wet soil, and calculate the dehydration rate of the agent for the soil slurry based on the moisture content of the wet soil; the agent is at room temperature and pressure, Zn 2+ The solidification removal rate reaches 98.8%, and the soil slurry dehydration rate can reach 95.6%.
[0034] Embodiment 2:
[0035] (1) Surface modification of fly ash
[0036] Weigh 20.000g of fly ash and add 800.000g of deionized water and 60.000g of 7% by mass dilute hydrochloric acid solution to soak for 4h, let stand and filter, then add 800.000g of deionized water and 40.000g of sodium hydroxide to soak for 4h, let stand and filter, add 1600.000g of deionized water to wash three times, filter and place in an oven at 100°C to dry for 6h to obtain fly ash after acid and alkali washing, then measure 2mL of fly ash after acid and alkali washing and place it in a plasma surface treatment instrument, first evacuate the plasma surface treatment instrument, then fill it with 80mL of oxygen, and then perform surface treatment under the conditions of an input voltage of 220V, a working distance of 12mm, and a plasma flame scanning rate of 100mm / s to obtain surface-modified fly ash, and repeat the plasma surface modification steps until the fly ash after acid and alkali washing is used up;
[0037] (2) Rhodamine B grafting
[0038] 2.500 g of rhodamine B was weighed and dissolved in 150.000 g of ethanol to form a rhodamine B solution, and then 0.500 g of tetraethyl orthosilicate was weighed and added to the rhodamine B solution, and the mixed solution was placed on a magnetic heating stirrer and stirred at 35° C. for 2 h, and then 25.000 g of a 7% by mass dilute hydrochloric acid solution was added dropwise to hydrolyze and condense the tetraethyl orthosilicate to form a grafting solution, 10.000 g of the surface-modified fly ash obtained in step (1) was weighed and placed in the grafting solution for 10 seconds, then filtered out and placed in an oven for low-temperature drying at 40° C. for 3 h, and the surface-modified fly ash was repeatedly placed in the grafting solution and dried until the grafting solution was consumed, and finally placed in a muffle furnace for low-temperature baking at 200° C. for 2 h to form a mixed substrate;
[0039] (3) Integrated pharmaceutical preparation
[0040] Weigh 0.455 g of starch and add 18.200 g of deionized water to form a starch slurry, heat it in a water bath at 95° C. for 2 h, and then cool it to room temperature. Then add 0.200 g of ammonium cerium sulfate, 4.545 g of acrylonitrile monomer and 10.000 g of the mixed base prepared in step (2), and place the mixed slurry on a magnetic heating stirrer and heat it in a water bath at 40° C. for reaction for 2 h. After the reaction is completed, add 27.300 g of acetone and continue stirring. Finally, let it stand for 4 h, filter it, and dry it in an oven at 60° C. for 6 h to obtain a fly ash-based dredged sludge dehydration and solidification integrated agent.
[0041] (4) Performance evaluation test
[0042] Take 100g of soil slurry (where the mass concentration of soil is 40%, ZnCl 2 10g of the integrated agent was added and stirred for 3min until the agent absorbed the water in the slurry. Then 10g of wet soil was placed in 100g of deionized water and stirred for 1h to form a purified soil slurry. Then, an inductively coupled plasma mass spectrometer was used to determine the Zn content in the purified soil slurry. 2+ The ion concentration is calculated from Zn 2+ Solidification removal rate, then take 10g of wet soil and place it in an oven at 100℃ for 10h to dry it, then calculate the moisture content of the wet soil, and calculate the dehydration rate of the agent for the soil slurry based on the moisture content of the wet soil; the agent is at room temperature and pressure, Zn 2+ The solidification removal rate reaches 98.2%, and the soil slurry dehydration rate can reach 98.3%.
[0043] Comparative Example 1
[0044] (1) Preparation of medicine
[0045] Except that fly ash is not used as the base material when preparing the agent, other conditions are the same as those in Example 1;
[0046] (2) Performance evaluation test
[0047] Take 100g of soil slurry (where the mass concentration of soil is 40%, ZnCl 2 10g of the integrated agent was added and stirred for 3min until the agent absorbed the water in the slurry. Then 10g of wet soil was placed in 100g of deionized water and stirred for 1h to form a purified soil slurry. Then, an inductively coupled plasma mass spectrometer was used to determine the Zn content in the purified soil slurry. 2+ The ion concentration is calculated from Zn 2+ Solidification removal rate, then take 10g of wet soil and place it in an oven at 100℃ for 10h to dry it, then calculate the moisture content of the wet soil, and calculate the dehydration rate of the agent for the soil slurry based on the moisture content of the wet soil; the agent is at room temperature and pressure, Zn2+ The solidification removal rate reaches 62.4%, and the soil slurry dehydration rate can reach 88.1%.
[0048] (3) Contrast effect
[0049] Compared with Example 1, if fly ash is not used as the base in the preparation of the agent, the dehydration rate of the agent is slightly reduced, but the Zn 2+ The solidification removal rate is significantly reduced, which is mainly because starch-acrylonitrile graft copolymer is the main dehydration component in the agent, and some heavy metal ions may enter the fly ash pores. Without the fly ash substrate, the removal rate of heavy metal ions will be significantly reduced.
[0050] Comparative Example 2:
[0051] (1) Preparation of medicine
[0052] Except that rhodamine B was not used for grafting during the preparation of the agent, other conditions were the same as those in Example 2;
[0053] (2) Contrast effect
[0054] Compared with Example 2, if Rhodamine B grafting is not used during the preparation of the agent, stratification will occur between the starch-acrylonitrile grafted copolymer and the fly ash, that is, the starch-acrylonitrile grafted copolymer does not grow on the fly ash mixed base, which will cause physical stratification of the agent during transportation and use, making it impossible to accurately weigh the agent and determine the agent usage ratio, thereby affecting the use effect.
Claims
1. A fly ash-based dredged sludge dehydration and solidification integrated agent, characterized in that: The agent is prepared by using modified fly ash as a base, tetraethyl orthosilicate and rhodamine B as grafting agents, starch-acrylonitrile grafting copolymer as a dehydrating agent, and ammonium cerium sulfate as an initiator, and adopts a surface modification-low temperature roasting coating-reaction grafting combined method; based on the mass of the modified fly ash base, the mass percentage of the grafting agent is 10% to 30%, the mass percentage of the dehydrating agent is 20% to 50%, and the mass percentage of the initiator is 1% to 10%.
2. The fly ash-based dredged sludge dehydration and solidification integrated agent according to claim 1, characterized in that: Based on the mass of the fly ash substrate, the mass percentage of the grafting agent is 10% to 30%, the mass percentage of the dehydrating agent is 30% to 50%, and the mass percentage of the initiator is 1% to 2%.
3. The method for preparing the fly ash-based dredged sludge dehydration and solidification integrated agent according to claim 1, characterized in that: The preparation method of the drug is as follows: (1) Surface modification of fly ash The fly ash is soaked in an acid solution and an alkaline solution successively and then filtered, and then washed and dried in sequence after filtering to obtain pretreated fly ash, and the pretreated fly ash is treated with plasma to obtain modified fly ash; (2) Rhodamine B grafting Tetraethyl orthosilicate is added to rhodamine B solution and mixed, and then a dilute hydrochloric acid solution is added to hydrolyze and condense tetraethyl orthosilicate to form a grafting solution, and the surface-modified fly ash is placed in the grafting solution for 5 to 10 seconds, then filtered out and placed in an oven for drying, and finally calcined to form a mixed substrate; (3) Integrated pharmaceutical preparation After heating and cooling, add ammonium cerium sulfate, acrylonitrile monomer and the mixed base prepared in step (2) to the starch slurry, mix well and react, add acetone after the reaction is completed and continue stirring, finally let it stand for 2 to 4 hours and then filter and dry to obtain a fly ash-based dredged sludge dehydration and solidification integrated agent.
4. The preparation method according to claim 2, characterized in that: The dilute hydrochloric acid solution described in step (1) is a hydrochloric acid solution with a mass fraction of 3% to 7%, and the mass fraction of the sodium hydroxide solution is 1 to 10%; the soaking time is 4 to 8 hours; the drying temperature is 80 to 100° C., and the drying time is 6 to 12 hours.
5. The preparation method according to claim 2, characterized in that: The plasma surface treatment instrument described in step (1) is a Plasma clean-PL-5010 model. During the surface treatment, the input voltage is 220V, the working distance is 5-12mm, the treatment atmosphere is oxygen, and the plasma flame scanning rate is 20-100mm / s.
6. The preparation method according to claim 2, characterized in that: The mass ratio of rhodamine B to tetraethyl orthosilicate in step (2) is 1:(0.1-0.2); the dilute hydrochloric acid solution is a hydrochloric acid solution with a molar fraction of 3%-7%, and the mass ratio of tetraethyl orthosilicate to the dilute hydrochloric acid solution is 1:(50-100).
7. The preparation method according to claim 2, characterized in that: The drying temperature in step (2) is 25-40° C., and the drying time is 3-6 hours; the roasting temperature is 160-200° C., and the roasting time is 2-4 hours.
8. The preparation method according to claim 2, characterized in that: In step (3), the mass concentration of starch slurry is 1-10%, and the mass ratio of starch slurry to acrylonitrile is 3-8:
1.
9. The preparation method according to claim 2, characterized in that: In step (3), the starch is heated to 85-95°C for 2-4 hours and then cooled to room temperature; the reaction temperature is 20-40°C for 2-4 hours; the drying temperature is 40-60°C for 6-12 hours.
10. Use of the agent according to claim 1 in the field of dredged sludge dehydration and reduction.
Citation Information
Patent Citations
Sludge treatment agent and sludge treatment method
CN107586003A
Sludge conditioner
CN111995222A
Sludge fly ash ceramsite and preparation method thereof
CN112608131A
SVI of mixed liquor in aeration tank
GB8422936D0
METHOD FOR TREATING WASTE LIQUID CONTAINING beta-STARCH
JP2009072738A
